The regulatory effect and molecular mechanism of lncRNA Gm10451 on islet cell dysfunction in children with diabetes - Wang, Jiao; Zhang, Li-hai; Kang, Yu-ming; Wang, Xian-he; Jiang, Chun-yu (Frontiers in Genetics, 2022)
The dysfunction of islet β-cells is one of the causes of diabetes, and lncRNA Gm10451 is also a participant in the occurrence and the development of various diseases. This study was carried out to reveal the correlation within β-cells and Gm10451. Our study was started with the cellular cultivation of MIN6 cells in vitro, where this islet β-cell line was randomly divided into the groups of control, hyperglycemia, Gm10451 siRNA tansfection, and Gm10451 tansfection. Of all these treatments, cells in the groups of Gm10451 siRNA tansfection and Gm10451 tansfection were given with lentiviral transfection under hyperglycemia condition. Further explorations were established using PCR assay and MTT method to evaluate Gm10451 expression and estimate cellular proliferation. It ended up with the enzyme-linked immunosorbent assay (ELISA) to assess Caspase 3 activity, superoxide dismutase (SOD) activity, and reactive oxygen species (ROS) content and the secretion of IL-10 and IL-1. It was found that Gm10451 expression in MIN6 cells under hyperglycemia cultivation was notably higher than the control group; likewise, a transfection with the lentivirus of Gm10451 also resulted in the upregulation of Gm10451 expression, succeeded with inhibiting cellular proliferation, enhancing Caspase 3 activity, and decreasing SOD activity. In the lentivirus transfection groups, transfection of Gm10451 elevated the ROS content and promoted IL-1 expression, and it also decreased both IL-10 expression and insulin secretion, leading to a consequence of statistically significant difference in contrast to the high-glucose group; on the contrary, transfection of Gm10451 siRNA in a high-glucose environment downregulated the expression of Gm10451 and inversed those change before, whose results were statistically significant when compared with the high-glucose group. Hyperglycemia promotes the expression of Gm10451. Targeting inhibition toward Gm10451 alleviates cellular apoptosis and the oxidative stress of islet cells, promoting proliferation and insulin secretion of islet cells.